2021
DOI: 10.3171/2021.9.focus21464
|View full text |Cite
|
Sign up to set email alerts
|

Spinal anesthesia in awake surgical procedures of the lumbar spine: a systematic review and meta-analysis of 3709 patients

Abstract: OBJECTIVE Awake surgery has previously been found to improve patient outcomes postoperatively in a variety of procedures. Recently, multiple groups have investigated the utility of this modality for use in spine surgery. However, few current meta-analyses exist comparing patient outcomes in awake spinal anesthesia with those in general anesthesia. Therefore, the authors sought to present an updated systematic review and meta-analysis investigating the utility of spinal anesthesia relative to general anesthesia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Perez-Roman et al conducted a meta-analysis of 3709 patients undergoing SA for lumbar discectomies and laminectomies. Also, they concluded that patients who underwent SA had decreased total anesthesia time, operative time, and post-operative complications [ 12 ]. Meng et al replicated these findings [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Perez-Roman et al conducted a meta-analysis of 3709 patients undergoing SA for lumbar discectomies and laminectomies. Also, they concluded that patients who underwent SA had decreased total anesthesia time, operative time, and post-operative complications [ 12 ]. Meng et al replicated these findings [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…There have been a few studies trying to compare the results of GA vs SA in spine surgery; most have been meta-analyses ( Perez et al, 2021 ). It will be important to have more robust studies such as matched cohort studies or randomized control studies.…”
Section: Discussionmentioning
confidence: 99%
“…Awake spinal surgeries including endoscopic procedures have become the “go-to” option for patients and neurosurgeons due to enhanced recovery. [ 17 ] This is currently employed for laminectomies with or without microdiscectomies, foraminotomies, anterior cervical discectomy and fusions, lumbar fusions, and dorsal column stimulator placements. [ 18 ]…”
Section: A) Newer Advancements In Neuroanaesthesiamentioning
confidence: 99%